A bibliometric analysis of cyber security and cyber forensics research - Sharma, Deepak; Mittal, Ruchi; Sekhar, Ravi; Shah, Pritesh; Renz, Matthias (Results in control and optimization, 2023)
Cybersecurity is one of the most important concerns associated with ever expanding internet based technologies, products, services and networks. If cybersecurity is prevention then cyber forensics is the cure. Both are equally important pillars of digital security. This paper presents an extensive bibliometric analysis of cybersecurity and cyberforensic research published in Web of Science during the past decade (2011–2021). The analysis included yearly publications, publication types and trends across different verticals such as publishing sources, organizations, researchers, countries and keywords. Full counting method was used for citation analysis, whereas fractional counting method was implemented to analyze co-citation, co-author collaborations as well as keyword co-occurrences across all these verticals. Furthermore, timeline and burst detection analyses were carried out to unravel significant topic trends and citations in the last decade. The study presents bibliometric results in terms of the authors, organizations, countries, keywords, sources and documents with the highest collaborative link strengths worldwide in the field of cybersecurity and forensics. Latest trends, under-investigated topics and future directions are also presented.